Diagnostic Usefulness of Dual-Energy Computed Tomography in Evaluation of the Severity of Acute Pulmonary Thromboembolism - Sung Min Moon (대한영상의학회지, 2015)
Purpose To evaluate the usefulness of dual-energy computed tomography (DECT) in severity assessment of patients with acute pulmonary thromboembolism (APTE).